Elevated interleukin-8 enhances prefrontal synaptic transmission in mice with persistent inflammatory pain - Cui Guang-bin; An Jia-ze; Zhang Nan; Zhao Ming-gao; Liu Shui-bing; Yi Jun (SAGE Publishing, 2012)
Abstract Background Interleukin-8 (IL-8) is known for its roles in inflammation and plays critical roles in the development of pain. Its expression increases in the brain after peripheral inflammation. Prefrontal cortex, including the anterior cingulate cortex (ACC), is a forebrain structure known for its roles in pain transmission and modulation. Painful stimuli potentiate the prefrontal synaptic transmission, however, little is known about the expression of IL-8 and its role in the enhanced ACC synaptic transmission in animals with persistent inflammatory pain. Findings In the present study, we examined IL-8 expression in the ACC, somatosensory cortex (SSC), and the dorsal horn of lumbar spinal cord following hind-paw administration of complete Freund's adjuvant (CFA) in mice and its effects on the ACC synaptic transmission. Quantification of IL-8 at protein level (by ELISA) revealed enhanced expression in the ACC and spinal cord during the chronic phases of CFA-induced peripheral inflammation. In vitro whole-cell patch-clamp recordings revealed that IL-8 significantly enhanced synaptic transmission through increased probability of neurotransmitter release in the ACC slice. ACC local infusion of repertaxin, a non-competitive allosteric blocker of IL-8 receptors, notably prolonged the paw withdrawal latency to thermal radian heat stimuli bilaterally in mice. Conclusions Our findings suggest that up-regulation of IL-8 in the ACC partly attributable to the enhanced prefrontal synaptic transmission in the mice with persistent inflammatory pain.